Climate inaction and managerial sensemaking: The case of renewable energy. (3rd June 2020) - Busch, Timo; Richert, Marcel; Johnson, Matthew; Lundie, Sven
Abstract: While business responses to climate change have been well researched on the organizational and institutional levels, the corporate strategic behavior on the microlevel—that ranges from proactivity to climate inaction—remain under‐researched. This article explores the individual determinants that affect the sensemaking phases, scanning, interpretation, and action, concerning the installation of on‐site renewable energy technologies. We investigate the extent to which managerial sensemaking is affected by different perceptions, motives, and skills in relation to renewable energy. By doing so, we uncover the individual determinants that affect decisions to either accept or reject the installation of renewable energy technologies. We contribute to the literature on business responses to climate change by deriving several key individual determinants on the microlevel, including technological expertise, sustainability orientation, time perspective, and economic growth attitude, which affect managers' sensemaking. Thus, we offer a framework to illustrate how these individual characteristics can lead either to proactive business responses or conversely to climate inaction.